2016
DOI: 10.7863/ultra.15.02051
|View full text |Cite
|
Sign up to set email alerts
|

Automated Estimation of Melanocytic Skin Tumor Thickness by Ultrasonic Radiofrequency Data

Abstract: The efficient automated tumor thickness measurement method developed could be used as a tool for preoperative assessment of melanocytic skin tumor thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
(121 reference statements)
0
15
1
Order By: Relevance
“…High‐frequency ultrasonic examination usually is used for the thickness evaluation of skin tumours. Good agreement with histologically evaluated thicknesses was observed in most studies . In this study, all cases of histologically diagnosed melanomas in situ were estimated as MST with thicknesses 0.01‐1.00 mm by analysing ultrasound images.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…High‐frequency ultrasonic examination usually is used for the thickness evaluation of skin tumours. Good agreement with histologically evaluated thicknesses was observed in most studies . In this study, all cases of histologically diagnosed melanomas in situ were estimated as MST with thicknesses 0.01‐1.00 mm by analysing ultrasound images.…”
Section: Discussionmentioning
confidence: 53%
“…[13][14][15][16] In our previous study we proposed to use analysis of raw ultrasonic signals for the evaluation of up to 1 mm thickness MST. 17 In this study, we hypothesized that the analysis of SIAgraphs can provide the information which correlate with MST penetration or thickness. So, the purpose of this study is to evaluate the diagnostic value of SIAscopic features for MST diagnosis at different thickness.…”
Section: Several Authors Shows Different Results Of Melanoma Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of Jasaitiene et al [7] and the recent studies [3,5,8,[9][10][11][12][13][14][15][16] showed a good correlation between pT and manually (mT) measured US thickness of MST using a 20-100 MHz transducer (Table 1). An overestimation of mT resulting from the impossibility of differentiating lymphocytic infiltrate or underlying melanocytic nevus cells from CM tissue has been reported in most studies [3,5,[9][10][11].…”
Section: Introductionmentioning
confidence: 86%